Investigation of microstructure and mechanical properties of SiC/Al surface composites fabricated by friction stir processing. (23rd August 2019) - Tang, Jingming; Shen, Yifu; Li, Junping
Abstract: In this investigation, the surface aluminum matrix composites (SAMCs) was fabricated by four-pass friction stir processing (FSP) with SiC particles as the reinforcing phase and 1060 aluminum alloy as the matrix. The effects of FSP parameters on the microstructure, phase compositions and wear behavior of the SAMCs were investigated in detail. The bonding mechanism between Al and SiC was analyzed. The SiC particles have the best refinement and distribution results in the SAMCs when the rotational speed and traverse speed of the tool are 950 rpm and 60 mm min −1, respectively. The bonding between SiC and Al was the direct bonding by the mechanisms of diffusion and inlay. The microhardness and friction coefficient of the SAMCs were significantly affected by the size and distribution of the SiC particles. The maximum microhardness of the SAMCs is about 105 HV, which is approximately 4 times that of matrix. However, the lowest friction coefficient of SAMCs is about half of the matrix. The refined SiC particles and the excellent interfacial bonding between the SiC particles and the matrix changed the wear mechanism from severe adhesive wear to mild abrasive wear.